EFEK LITERASI KEUANGAN TERHADAP PERENCANAAN DAN PERILAKU KEUANGAN SISWA KELAS XII SMA NEGERI 1 KOTA JAMBI - Salsabila; Mayasari; Sudawan Supriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Financial literacy is an important competency that students need to possess in order to manage their finances wisely amid the rapid development of digital financial services. This study aimed to analyze the effect of financial literacy on financial planning and financial behavior of twelfth-grade students at SMA Negeri 1 Kota Jambi. This research employed a quantitative approach using a survey method. The population consisted of all twelfth-grade students of SMA Negeri 1 Kota Jambi, with a sample of 188 students selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed using Multivariate Analysis of Variance (MANOVA) with SPSS version 22. The results showed that financial literacy had a positive and significant effect on financial planning, with an F value of 138.132 and a significance value of 0.001 < 0.05. Financial literacy also had a positive and significant effect on financial behavior, with an F value of 146.220 and a significance value of 0.001 < 0.05. The MANOVA test showed a Pillai’s Trace value of 0.609, indicating that financial literacy simultaneously affected financial planning and financial behavior. These findings indicate that higher financial literacy levels contribute to better financial planning and more responsible financial behavior among students. Keywords: Financial Literacy, Financial Planning, Financial Behavior